METHODS USED IN DETERMINING THE AGE OF BRUISES - Kostadinova Petrova, Irena; Janeska, Biljana; Mitevska, Elida; Milenkova, Liljana; Kostovska, Nevena; Peneva E (SHMSHM - AAMD, 2015)
Bruises are common skin lesions that can be found in persons died a violent death and therefore have a forensic significance. In practice there are cases of violent death when it is difficult to determine with certainty the age of the bruises. But according to the biological processes associated with the reparation of the bruises, we could get reliable information about their age. Common methods for determining the age of the bruises, such as observation, colorimetry, spectrophotometry and patho-histological analysis are presented in this review paper. Determination of the age of bruises according to their color is a method used by most experts in the initial analysis. The observation of the yellow color, not brown or orange, points out a bruise that is not fresh. However, the possibility of visual observation is limited by the morphology and physiology of the human eye. Spectrophotometric analysis of data can offer useful and objective information. Histological analysis is suitable as a method only in post-mortem examinations. In this field of work there is a lack of published information on the histological analysis about the aging of bruises, which restricts the information for more precise determination of their age
Методи за одредување на староста на крвните подливи
Keywords: bruises; methods for determining the age of bruises